The Effect of Diversification and Funding Decisions on Company Performance and Corporate Value with Good Corporate Governance (GCG) as Moderated Variable - Suchandiko, Elmayola; Efni, Yulia; Rokhmawati, Andewi (Program Pascasarjana, Universitas Riau, 2021)
This study aims to analyze the effects of diversification and funding decisions on company performance and value of companies with Good Corporate Governance (GCG) as a moderating variable in an industrial manufacturing company listed on the Stock Exchange (IDX) in 2013-2017. Sampling method using purposive sampling techniques and accounting 41 manufacturing industry companies. Samples were analyzed by using PLS. The results of this study indicated that diversification has no significant significant effect on firm value. Funding decisions have a significant effect on the value of the company. The company's performance significantly influences the value of the company. The funding decision has a significant influence on the company's value through indirect. Diversification has a significant influence on the company's value through indirect. GCG has no significant effect in moderating the influence of funding decisions on firm value. GCG has a significant effect in moderating the effect of diversification on firm value.Keywords: Diversification, Financial Decision, Financial Performance, Firm Value, Good Corporate Governance